Student’s Science Literacy in the Aspect of Content Science? (Jurnal Pendidikan IPA Indonesia, 2017)
The fundamental issue is the growing use of scientific information possessed by students to solve problems in daily life and produce useful scientific source from scientific literacy. The purpose of the research was to analyze and describe the ability of a student science concepts from the aspect of scientific literacy that includes aspects of scientific knowledge, scientific competence, scientific context as well as the factors that influence the students’ science literacy skills. This research was quantitative descriptive analysis. The instrument used was a matter of objective 40 along with the reasons of the physics concept and biology concepts that are used to measure aspects of scientific knowledge, scientific competence, and scientific context, while the students’ attitudes towards science and science teaching and learning strategies measured by questionnaire instrument. Instruments used included multiple-choice test questions reasoned and questionnaires (the attitude of science and science teaching and learning strategies). Based on data analysis it was known that the ability of science literacy PGSD UMK students varied, 66.2% of students were at the level of nominal and 33.8% of the students were at the functional level. It showed that 66.2% of students already had a concept for connecting science with other disciplines, could write a scientific term, but students still had misconceptions, while 33.8% of students considered the theory and explained concepts correctly, but they had a limited understanding and were difficult to connect to the concept of his own opinion.